Pengaruh Kualitas Layanan Berbasis Artificial Intelegence, Religiusitas,Trust Terhadap Loyalitas Nasabah Perbankan Syariah Cabang Malang Unisma - Mariati, Mariati; Basalamah, Muhammad Ridwan; Rahmawati, Rahmawati (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The Islamic banking industry in Indonesia continues to grow rapidly supported by technological advances and financial inclusion policies. This study aims to analyse the effect of Artificial Intelligence (AI)-based service quality, religiosity, and trust on customer loyalty of Bank Syariah branch Malang Unisma. The research method uses quantitative methods, the method used is multiple linear regression, this study collected data from 80 respondents who are customers of the Islamic bank. The variables studied include AI-based service quality, religiosity and trust. The results showed that AI-based service quality partially had a positive but insignificant effect on customer loyalty, religiosity and trust partially had a positive and significant effect on customer loyalty.This study confirms the importance of religiosity and trust in building customer loyalty in Islamic banks. customer loyalty in Islamic banks, while AI technology provides added value to the quality of services offered. added value to the quality of services offered. The findings provide new insights into the role of digital transformation and religious values in strengthening customer loyalty in Islamic banking in Indonesia. Keywords: Islamic Banking, Artificial Intelligence, Religiosity, Trust, Customer Loyalty, Digital Transformation, Service Quality.